2015
DOI: 10.1007/s10528-015-9680-2
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the CETP TaqIB and ApoE Polymorphisms in Southern Thai Subjects with the Metabolic Syndrome

Abstract: Several genetic factors have been investigated responsible for metabolic syndrome (MetS). The aim of this study was to investigate the association between cholesteryl ester transfer protein (CETP) TaqIB and apolipoprotein E (ApoE) polymorphisms and MetS in 378 subjects from Southern Thailand. Subjects were divided into MetS+ (n = 121) and MetS- (n = 257) groups according to the criteria of National Cholesterol Education Program Adult Treatment Panel III (NCEP ATPIII). The CETP TaqIB and ApoE polymorphisms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
1
9
4
Order By: Relevance
“…This is consistent with Anton et al [36] who hold that the risk of MS was reduced by 32% ( p = 0.005, OR = 0.68) in carriers of the B 2 variant. However, this was different from observations by Jeenduang [38] and Maroufi [39]. …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is consistent with Anton et al [36] who hold that the risk of MS was reduced by 32% ( p = 0.005, OR = 0.68) in carriers of the B 2 variant. However, this was different from observations by Jeenduang [38] and Maroufi [39]. …”
Section: Discussioncontrasting
confidence: 99%
“…The rs12149545-A frequency was 29.1%, and the rs711752-A frequency (46.8%) was similar to that in Latvians (46.2%) [21]. For rs708272, the rs708272-T frequency (46.8%) was higher than that in Austria (41.3) [36], Turkey (43%) [37], or Southern Thailand (37.43%) [38]. Moreover, rs708272-T plays an inactive role in the development of MS.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the allele frequencies of CETP TaqIB polymorphisms (B1 45.78%, B2 54.22%) in this study were similar to the Indian (B1 41.8%, B2 58.2%) population. In contrast, our results were different from Thai (B1 62.57%, B2 37.43%), Chinese (B1 62.8%, B2 37.2%), and Japanese (B1 62%, B2 38%) populations . This suggests that our study population may be genetically different from the general population among Thais and other ethnic groups.…”
Section: Discussioncontrasting
confidence: 94%
“…Previous studies have also reported that E4 allele is generally associated with increased plasma cholesterol and LDL‐C, and E2 allele is associated with decreased plasma cholesterol and LDL‐C compared with the E3 allele . The allele frequencies of the APOE polymorphisms (E2 7.11%, E3 79.56%, E4 13.33%) in this study were similar to previous reports among the Thai population (E2 7.18%‐10.42%, E3 77.04%‐77.51%, E4 12.54%‐15.43%) . APOE4 allele in our study was higher than Japanese (10.5%), Han Chinese (7.5%), Taiwanese (7.5%), and Korean (9%) populations but lower than the Malaysian population (20.20%) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation